If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 3(-2 + 4) = 5 Combine like terms: -2 + 4 = 2 -1x + 3(2) = 5 Multiply 3 * 2 -1x + 6 = 5 Reorder the terms: 6 + -1x = 5 Solving 6 + -1x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 5 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 5 + -6 -1x = 5 + -6 Combine like terms: 5 + -6 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| p/6=20 | | -3.36=b+5.12 | | b-5+3b=32 | | -7x-8+9x=4 | | 5x+3=x+4 | | a=2l+2w | | -6x+6=4(2x+1) | | x^2+15x-2=0 | | 4.5=15+15x | | -23=34*t | | (25)-(-5)= | | a=21+2w | | b-8+8b=29 | | 15y=14+2(5y+6) | | 10(6x+11)= | | 6x+6=4(2x+1) | | 4lnx=20 | | -10x-11+12x-15=-4 | | 4-(3x+6)=-10 | | 5(x-8)=-11 | | b/13-9b/13=40/13 | | 12x-4=24x+4 | | (-2)+2(12)=a | | -10x-11+12x-15=4 | | 3y+4-y=10+y | | 3.2g+6=6+3.2g | | -4x-2(3x-7)=-6 | | 22a-2a+43.465=3a | | 3y-1+4y=8-9+7y | | 4=4(1-4x)+8(x-4) | | 3[-4-(-4+5)]= | | 3(y-8)=-y |